2020
DOI: 10.1063/5.0012453
|View full text |Cite
|
Sign up to set email alerts
|

Current driven chiral domain wall motions in synthetic antiferromagnets with Co/Rh/Co

Abstract: Spin–orbit torque that originates from spin Hall effect and Dzyaloshinskii–Moriya interaction (DMI) can efficiently move chiral magnetic domain walls in perpendicularly magnetized wires. It has been shown that antiferromagnetically coupled composite domain walls across a ruthenium layer can be driven even faster by exchange coupling torque that is proportional to exchange coupling strength. Here, we report a current-driven motion of composite chiral domain walls in synthetic antiferromagnets with a rhodium spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In particular, very fast DW motion at several 100 m s −1 for high current drives of a few TA m −2 have been observed in these systems using a Ru spacer [12]. It has subsequently been shown that replacing the spacer material with Rh reduces the DW velocity [13], that DW velocity in a SAF can be controlled by means of iontronic gating [14], and that SAF nanowires can be connected to conventional FM wires and still transmit DWs [15]. A variety of effects related to curved tracks, disordered materials, and temperature fluctuations have been studied by means of micromagnetics [16].…”
Section: Introductionmentioning
confidence: 90%
“…In particular, very fast DW motion at several 100 m s −1 for high current drives of a few TA m −2 have been observed in these systems using a Ru spacer [12]. It has subsequently been shown that replacing the spacer material with Rh reduces the DW velocity [13], that DW velocity in a SAF can be controlled by means of iontronic gating [14], and that SAF nanowires can be connected to conventional FM wires and still transmit DWs [15]. A variety of effects related to curved tracks, disordered materials, and temperature fluctuations have been studied by means of micromagnetics [16].…”
Section: Introductionmentioning
confidence: 90%
“…However, the anti-ferromagnetic behavior—what is referred to as a synthetic antiferromagnet (SAF)—is of particular technological interest to spintronic applications as the building block of a fringe-field free reference layer for ultrahigh density spin-transfer-torque magnetic random access memory (STT-MRAM) cells 11 , 12 . Additionally, the SAF shows technological merit as the free layer for SAF magnetic tunnel junctions (MTJs) 20 , 28 , 29 and as domain wall and Skyrmion bubble devices 30 , 31 , in which case the IEC torques can generate faster magnetization switching, enable high domain wall velocities and stabilize Skyrmions at elevated temperature compared to ferromagnetic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Significant ongoing research efforts in spintronic applications are focused on the development and processing of synthetic antiferromagnets (SAFs), the trilayered FM1/NM/FM2 structure, where FM is a ferromagnet and NM is typically an ultrathin (<1 nm) nonmagnetic metal that typically includes Cr, Ru or Ir . The interlayer exchange coupling (IEC) across the NM layer shows an oscillatory and decaying behavior that can be ferromagnetic (FM) or anti-FM, but the anti-FM behavior is of particular technological interest to spintronic applications as the building block of a fringe-field free reference layer for ultrahigh density spin-transfer-torque magnetic random access memory (STT-MRAM) cells. , Additionally, the SAF shows technological merit as the free layer for SAF magnetic tunnel junctions (MTJs) and as domain wall and Skyrmion bubble devices, , in which case the IEC torques can generate faster magnetization switching, enable high domain wall velocities, and stabilize Skyrmions at elevated temperature compared to FM counterparts. Furthermore, SAFs are believed to deliver topological protection for energy efficient spin–orbit torque MRAM devices, including protection of chiral Neel-type domain walls in domain wall and Skyrmion racetrack memory devices by potentially reducing or eliminating the deleterious Skyrmion Hall effect. , …”
Section: Introductionmentioning
confidence: 99%